"Imagine All the People": Imagined Interactions in Virtual Reality When Public Speaking. (March 2021) - LeFebvre, Leah E.; LeFebvre, Luke; Allen, Mike
This study explores the relationship between public speaking anxiety (PSA) and Imaginary Interactions (IIs). Participants ( N  = 17) were recruited from the multi-section departmental introductory public speaking course. Virtual reality (VR) as a potential form of II treatment for PSA blurs the reality between imagined and actual interactions. This study utilized a sequential explanatory approach to examine inferential and descriptive findings. The inferential investigation employed a four-stage design requiring participants to complete pre-test PSA and post-test assessments before and after VR simulations, exploring II functions and attributions. The follow-up descriptive analysis expanded and generated new understanding for the complexities of II through participants' experiences using directed content analysis. Utilizing VR as an extension of IIs highlighted the rehearsal function, and variations in attributions for discrepancy and specificity between VR realism and artificial simulated perceptions. The implications suggest that VR provides students in public speaking environments a treatment mechanism that minimizes the cognitive strain to imagine the scene and setting of the situation, while simultaneously providing assistance in PSA reduction.